Comprehensive network pharmacology and experimentation to unveil the therapeutic efficacy and mechanisms of gypenoside LI in anaplastic thyroid cancer - Meiyu Liu; Haidong Liao; Qin Peng; Junwei Huang; Weixiang Liu; Mengqiao Dai; Zanbing Li; Yang Xie; Jiafeng Liu; Yong Ying; Xiangtai Zeng (BMC Cancer)
Abstract Background Anaplastic thyroid cancer (ATC) is a markedly invasive subtype of thyroid cancer with a poor prognosis. The Gynostemma pentaphyllum-derived Gypenoside LI (Gyp LI) can inhibit the growth and metastasis of various tumors. This study was designed to evaluate the pharmacological mechanisms of Gyp LI against ATC via network pharmacology analysis combined with experimental verification. Methods Core targets and signaling pathways were obtained by using the network pharmacological analysis method. Utilizing a combination of in vitro and in vivo methodologies, we conducted a rigorous examination to ascertain the suppressive impact of Gyp LI on the ATC cell lines, specifically 8305 C and C643. Then used western blotting and immunohistochemistry to analyze the inhibitory effects of Gyp LI on SRC kinase and its downstream signaling pathways. Results Through integrative analysis of Gyp LI and ATC-target interactions, 78 candidate targets were identified. Network-based protein-protein interaction (PPI) analysis, combined with molecular docking, pinpointed HSP90AA1, SRC, and CASP3 as pivotal hub genes modulated by Gyp LI. KEGG enrichment analysis further emphasized the PI3K/AKT pathway, highlighting its critical involvement in ATC therapy. Gyp LI significantly inhibits ATC cell proliferation, migration, and invasion while inducing apoptosis, likely via modulation of the SRC/PI3K/AKT axis. Moreover, it enhances iodine uptake in ATC cells by regulating the sodium-iodide symporter pathway. Conclusions Gyp LI effectively inhibits ATC progression by modulating SRC/PI3K/AKT signaling, enhancing apoptosis, and promoting iodine uptake, offering potential therapeutic benefits for ATC treatment.